ANALISIS EFEKTIFITAS PROGRAM MAGANG UNTUK SINKRONISASI LINK AND MATCH PERGURUAN TINGGI DENGAN DUNIA INDUSTRI (Studi Terhadap Program Magang Mahasiswa Program Studi Administrasi Bisnis Politeknik Negeri Madiun) - Lisdiantini, Netty; Azis, Aminudin; Syafitri, Eva Mirza; Thousani, Hifzhan Frima (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2022)
This research was conducted to determine the effectiveness of the internship program for link and match between universities and the industrial world. This study uses a qualitative method based on the assumption that qualitative research emphasizes the nature of naturalism, meaning that the emerging reality becomes the study material in this study so that the object of research and problems regarding the analysis of the effectiveness of the internship program for synchronizing link and match universities with the business world of the industrial world will be disclosed. in detail and depth. Researchers also do not give treatment or treatment to the object, so that the object is left as it is in its original condition. From the results of the study, it can be concluded that the effectiveness of the internship carried out was assessed by the company and the student interns as having been effective, lack of technical skills (computers and operating facilities), soft skills (communication, adaptation, interaction, work discipline) and the need to improve technical skills such as operating computers, English, soft skills such as communication, discipline, ethics and adaptation and interaction.Keywords: link and match, internship, effectiveness